The biological content accuracy of natural science textbooks for VIII grade - Puspa Mega Candra; Ixora Sartika Mercuriani; Endik Deni Nugroho; V. Vlorensius (University of Muhammadiyah Malang, 2020)
The properness of concepts, principles, and biological contents of natural science textbooks is essential. The aim of this research was to compare the biology content of natural science textbooks for VIII graders in second semester. The indicators used to determine the properness were the accuracy of Core Competence/CC and Basic Competence/BC, concept, principle, illustration, and word editing. The textbooks analyzed were those which published by Indonesian Ministry of Education and Culture (government) and private publisher. The sample of this qualitative descriptive research was three natural science textbooks which applied Curriculum 2013. The research procedure referred to Milies and Huberman. The results showed that the properness percentages of CC and BC of science textbook published by governmental and private publisher were 86.25% (excellent) and 74.28% (good) respectively. There were inaccuracy of 11 concepts, 1 principle, and 5 illustrations found in the textbooks published by governmental. Furthermore, there were 5 inaccurate concepts found in the textbook published by private publisher. Moreover, there were 37 typographical errors found in the Natural Science Textbooks published by government and none found in the book published by private publisher. Therefore, the textbooks published by private publisher is better than those which by govermental publisher.